Electronic money: advantages, disadvantages, impact on the monetary system - V. A. Varfolomeeva (Путеводитель предпринимателя)
The article discusses the concept, types of electronic money systems. The purpose of the article is to study the essence and influence of electronic money on the monetary system. The article focuses on the history of the emergence of electronic money, as well as statistical data on their use directly in payments. The authors came to the conclusion that the use of electronic money will affect monetary policy, banking supervision, the definition of money supply, monetary aggregates.